The Effect of Traditional Games (Congklak) on Cognitive and Fine Motor Development in Children Under Five - Rukmini, Rukmini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: In theory, games can be used as a stimulus for optimizing brain development in children under five. Traditional game may be useful to improve brain development. This study aimed to analyze the effect of traditional games (congklak) on cognitive and fine motor development in children under five. Subjects and Method: This was a quasi-experiment study with pre and post-test design conducted at Gembong Sawah, Surabaya, East Java, in February 2021. A total of 33 childrens under five was selected by random sampling. The dependent variable were cognitive and fine motor development. The independent variable was traditional game (congklak). The data were collected by a set of questionnaire and analyzed by Wilcoxon. Results: Cognitive development on children under five was higher after intervention (Mean= 34.72; SD= 6.07) than before (Mean=26.88; SD= 6.12) and it was statistically significant (p<0.001). Fine motor development in children under five (Mean= 24.58; SD= 3.96) was higher than before (Mean=18.52; SD= 4.61) and it was statistically significant (p<0.001). Conclusion: Traditional game (congklak) effectively improves cognitive and fine motor development among children under five.